'Designer babies' almost thirty years on. Issue 1 (July 2018) - Handyside, Alan H
Abstract : The first pregnancies and live births following in vitro fertilisation (IVF) and preimplantation genetic testing (PGT), formerly known as preimplantation genetic diagnosis, were reported in 1990, almost 30 years ago, in several couples at risk of X-linked inherited conditions, which typically only affect boys inheriting the X chromosome with the affected gene from their carrier mothers. At that time, it was only possible to identify the sex of the embryo by amplifying a Y-linked repeat sequence in single cells biopsied at cleavage stages and avoid the transfer of males, half of which would be affected. The extensive publicity surrounding these cases and the perceived risk of using IVF and PGT for desirable characteristics not related to health, such as sex selection, led to the epithet of 'designer babies' which continues to resonate to this day. Here, I briefly reflect on how the technology of PGT has evolved over the decades and whether it deserves this reputation. With efficient methods for whole genome amplification and the genomic revolution, we now have highly accurate universal tests that combine marker-based diagnosis of almost any monogenic disorder with the detection of aneuploidy. PGT is now clinically well established and is likely to remain a valuable alternative for couples at risk of having affected children.